A three-dimensional haptic cataract tele-surgery simulation - Hamam, Abdelwahab (University of Ottawa (Canada), 2007)
Medical simulations are becoming more advanced and more reliable in training medical students and new surgeons. Especially in the context of delicate surgeries, such as cataract surgery, the medical community is shifting from traditional medical training to sophisticated virtual reality simulations. In this thesis, we present a simulation built in a three-dimensional environment that aids in training medical residents to perform cataract surgeries. The application utilizes haptic devices as a means of interaction, which enriches the application by providing a sense of touch and force-feedback to users. In addition, we discuss our modeling of the environment and the decisions undertaken in the design. We also compare this 3D application with similar applications in terms of functionality but with different user interfaces, and mention what was the eye surgeon's reaction towards each interface in the training simulation. Finally, we conclude with future modifications of the application and describe a future direction.
Keywords: Engineering, Biomedical.; Engineering, Electronics and Electrical.